2014
DOI: 10.4103/2230-8598.137704
|View full text |Cite
|
Sign up to set email alerts
|

The impact of severity of hypertension on auditory brainstem responses

Abstract: Background: Auditory brainstem response is an objective electrophysiological method for assessing the auditory pathways from the auditory nerve to the brainstem. The aim of this study was to correlate and to assess the degree of involvement of peripheral and central regions of brainstem auditory pathways with increasing severity of hypertension, among the patients of essential hypertension. Method: This study was conducted on 50 healthy age and sex matched controls (Group I) and 50 hypertensive patients (Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…They added that the delay in auditory processing time may be considered as an index of subclinical expression of visceral damage in hypertensive patients. 8 Jyoti et al, also showed prolongation of all absolute latencies of BAEP waves I and V in hypertensive group and strongly reported that the changes in hypertensive patients, can be due to multiple factors that include associated dyslipidemia, oxidative stress or arteriosclerosis leading to poor blood supply to different organs. 12 Haldwani et al, in their study found the relation between mean arterial pressure and BAEP latencies in hypertensive patients and they added that it provided an electrophysiological evidence of interaction of BP control mechanism in the brainstem with auditory pathway.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They added that the delay in auditory processing time may be considered as an index of subclinical expression of visceral damage in hypertensive patients. 8 Jyoti et al, also showed prolongation of all absolute latencies of BAEP waves I and V in hypertensive group and strongly reported that the changes in hypertensive patients, can be due to multiple factors that include associated dyslipidemia, oxidative stress or arteriosclerosis leading to poor blood supply to different organs. 12 Haldwani et al, in their study found the relation between mean arterial pressure and BAEP latencies in hypertensive patients and they added that it provided an electrophysiological evidence of interaction of BP control mechanism in the brainstem with auditory pathway.…”
Section: Discussionmentioning
confidence: 93%
“…Some found a relationship between hearing loss and hypertension but some not. [6][7][8] In this study we tried to find the effects of hypertension on BAEP and whether the increasing severity of hypertension also affects the amplitude and latency of…”
Section: Introductionmentioning
confidence: 99%
“…[5,6,7] Prolonged interpeak latencies have also been noticed in benign intracranial hypertensive patients and authors proposed stetchingcompression of cochlear nerve as a mechanism for this. [10] As far as correlation of waves of BAEPs with BP is concerned conflicting data is available.…”
Section: Discussionmentioning
confidence: 99%
“…Some have found a relationship between hypertension and hearing loss while some have not. [5], [6], [7] Results have been unclear, and there is the need for further studies as far as peripheral and central hearing are concerned in the affected population One of the studies has reported a correlation of peak latencies and interpeak latencies of waves of BAEPs with systolic and diastolic blood pressure [5] but data is still lacking, and its correlation with mean blood pressure has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…8 These central neuronal damage may alter electrical activity in the central nervous system and may affect various evoked potentials. 9 Evoked potentials are responses to stimulation of a sensory pathway in the nervous system. This comprise of stimulation of a sensory nerve in the limb (somatosensory evoked potentials-SSEPs), the visual system (visual evoked potentials-VEP) or the auditory system (brain stem auditory evoked potentials-BAEP or brain stem auditory evoked responses-BAER).…”
Section: Introductionmentioning
confidence: 99%